Aryl and heteroaryl nosylates as stable and cheap partners for Suzuki–Miyaura cross-coupling reactions. Issue 16 (21st April 2016) - Dikova, Anna; Cheval, Nicolas P.; Blanc, Aurélien; Weibel, Jean-Marc; Pale, Patrick
Abstract: Aryl and heteroaryl para -nitrophenylsulfonates (nosylates) have been successfully engaged for the first time in Suzuki–Miyaura cross-coupling reactions with various aryl or vinylboronic acids (48–98%, 12 examples). The best catalyst/ligand combination have been determined to be 2 mol % of palladium acetate (Pd(OAc)2 ) and 4 mol % of 2-dicyclohexylphosphino-2′, 4′, 6′-triisopropylbiphenyl (XPhos) using K3 PO4 as base, in tetrahydrofuran at 80 °C. These new reaction conditions notably provide a direct and very efficient access to the natural alkaloid dubamine. Graphical abstract: